Epidermal Growth Factor Receptor Exon 19 Deletion Subtypes Do Not Influence Survival Outcomes Following First-line Epidermal Growth Factor Receptor-tyrosine Kinase Inhibitors in Advanced Nonsmall Cell Lung Cancer Patients - Yan-Jei Tang; John Wen-Cheng Chang; Chen-Yang Huang; Yueh-Fu Fang; Ching-Fu Chang; Cheng-Ta Yang; Chih-Hsi Scott Kuo; Ping-Chih Hsu; Chiao-En Wu (Journal of Cancer Research and Practice)
Background: Several deletion and insertion subtypes occur in exon 19 of the epidermal growth factor receptor (EGFR) gene, collectively called exon 19 deletions (del19), and are one of the common EGFR mutations in nonsmall cell lung cancer (NSCLC). Previous studies have shown that del19 subtypes might influence the response to tyrosine kinase inhibitors (TKIs), but their findings have been inconsistent. Therefore, this study aimed to evaluate the impact of del19 subtypes in an Asian population and provide additional evidence on this issue. Materials and Methods: NSCLC patients treated at Chang Gung Medical Hospitals between 2011 and 2018 were retrospectively reviewed. Their clinicopathological characteristics, clinical tumor response, progression-free survival (PFS), and overall survival (OS) were collected. PFS was evaluated among different del19 subtypes and EGFR-TKIs. Results: This study included 164 patients with NSCLC carrying an EGFR del19 mutation who had detailed information about their del19 subtype and were treated with frontline EGFR-TKIs (39 with afatinib and 125 with gefitinib/erlotinib). In this cohort, del19 subtypes did not influence PFS and OS based on different classifications, including start codon of deletion, the number of deleted nucleotides, or pure deletion versus mixed deletion/insertion/substitution. In addition, afatinib generally showed better PFS than gefitinib/erlotinib, particularly and significantly for patients with the p. E746_A750 mutation, a common 15 nucleotide deletion, or a pure deletion without insertion/substitution. Conclusion: In this study, del19 subtypes did not influence PFS and OS with EGFR-TKIs. Afatinib showed better activity than first-generation TKIs and should be preferred for patients with del19 mutations.